QR Code-Based Vocabulary Practice and Its Effect on Speaking Skills: A Pre-Experimental Study at SMAN 1 Polewali - Damier, Wahyunida; Damier, Masyunida (Jurnal Ilmiah Multidisiplin Amsir, 2025)
Abstrak Penelitian ini dilakukan untuk menguji efektivitas pembelajaran kosakata harian berbasis QR Code dalam meningkatkan kemampuan berbicara siswa di SMAN 1 Polewali. Pendekatan eksperimental kuantitatif digunakan dalam penelitian ini dengan memanfaatkan desain tes awal dan tes akhir pada satu kelompok. Sebanyak 34 siswa kelas sebelas berpartisipasi dalam penelitian ini. Kemampuan berbicara dievaluasi melalui rubrik berbicara analitis yang mencakup lima komponen, yaitu pelafalan, kosakata, tata bahasa, kelancaran, dan pemahaman. Analisis data dilakukan menggunakan statistik deskriptif dan Uji Rangking Bertanda Wilcoxon. Hasil penelitian menunjukkan bahwa kemampuan berbicara siswa mengalami peningkatan yang signifikan setelah penerapan pembelajaran berbasis QR Code. Skor rata-rata yang diperoleh pada tes awal adalah 61,21, yang menunjukkan kemampuan berbicara awal yang relatif rendah, kemudian meningkat menjadi 82,14 pada tes akhir setelah perlakuan diberikan. Kata Kunci: QR, Kosakata, Berbicara Abstract This research was conducted to examine the effectiveness of QR Code-based daily vocabulary learning in enhancing students' speaking abilities at SMAN 1 Polewali. A quantitative experimental approach was employed, utilizing a single-group pre-test and post-test design. A total of 34 eleventh-grade students participated in this study. Speaking proficiency was evaluated through an analytic speaking rubric encompassing five components: pronunciation, vocabulary, grammar, fluency, and comprehension. Data analysis was performed using descriptive statistics and the Wilcoxon Signed Rank Test. The results demonstrated that students' speaking abilities improved markedly after the application of QR Code-based learning. The mean score obtained in the pre-test was 61.21, indicating relatively low initial speaking proficiency, which subsequently increased to 82.14 in the post-test following the treatment. Additionally, the percentage of students achieving the minimum speaking proficiency criterion (≥80) rose dramatically from 20% during the pre-test to roughly 90% during the post-test. A statistically significant difference was found between pre-test and post-test scores based on the Wilcoxon Signed Rank Test analysis (p < 0.05). These results demonstrate that QR Code-based daily vocabulary learning is effective in developing students' speaking skills and can be regarded as a practical teaching method in EFL classrooms. Keywords: QR Generator Code, Daily Vocabulary, Speaking Skill